Simultaneous Corneal Topography and Epithelial Thickness Mapping from a Single Measurement Using Optical Coherence Tomography - Sikorski, Bartosz L. (Journal of ophthalmology, 2022)
Purpose. To evaluate the performance of corneal epithelial thickness mapping (ETM) and demonstrate simultaneous measurement of ETMs and corneal topography using REVO NX (Optopol Technology, Zawiercie, Poland)—an OCT device for anterior and posterior segment imaging. Methods. One hundred thirty-seven eyes of 137 normal subjects and patients with corneal diseases were recruited to the study. Each subject was scanned with REVO NX. ETMs and corneal topography maps were reconstructed from a single measurement. Corneal topography was also carried out using Pentacam (Oculus, Wetzlar, Germany). One hundred twenty-eight eyes were qualified for the final analysis. Forty healthy eyes were used to evaluate the performance of ETM, and 88 eyes were used to compare ETMs and corneal topography. The repeatability and reproducibility of ETMs in healthy subjects were assessed on the basis of 17 spatial zones derived from an 8-mm diameter corneal scan using within-subject standard deviation, test-retest repeatability, within-subject coefficient of variation (CoV), and intraclass correlation coefficient (ICC). Results. The ICC for both repeatability and reproducibility of ETMs for the central sector was 0.95. The ICC value for the other sectors was only moderately lower. However, the CoV for repeatability (≤1.55%) was slightly higher than the value reported for the RTVue device (Optovue, Inc, Fremont, California, USA), for which a CoV in the central zone of 1.07% was reported in unoperated eyes. The superior quadrants were found to be the thinnest while the inferior ones were the thickest. ETMs and topography maps created from a single OCT measurement present a complementary image of the cornea. Conclusions. ETMs obtained using REVO NX show high levels of repeatability and reproducibility in normal eyes. Because the topographic and epithelial thickness analyses are performed using the same data, which means they are based on the exact same 3D corneal model, they do not require reciprocal centration and map matching. This ensures a complete point-to-point correlation between ETMs and corneal topography maps, which paints a fuller picture of a given pathology.